2018
DOI: 10.29252/jafm.11.06.29062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stenosis Severity on Wall Shear Stress Based Hemodynamic Descriptors using Multiphase Mixture Theory

Abstract: A variety of wall shear stress (WSS) based hemodynamic descriptors have been defined over the years to study hemodynamic flow instabilities as potential indicators or prognosticators of endothelial wall dysfunction. Generally, these hemodynamic indicators have been calculated numerically using 'single phase' approach. In single phase models, the flow-dependent cell interactions and their transport are usually neglected by treating blood as a single phase non-Newtonian fluid. In the present investigation, a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…The shape of the artery was a full cylindrical tube with a circular cross-section and an axisymmetric blockage (Figure 1). The selected diameter (3 mm) was based on the literature [40,41] and the length of the stenosis was defined as twice the normal diameter, an assumption applied by several researchers [42][43][44][45]. In addition, the length of the inlet zone (22 mm) was selected to ensure the creation of a fully developed inlet flow.…”
Section: Coronary Artery 3d Biomodels Design and Fabricationmentioning
confidence: 99%
“…The shape of the artery was a full cylindrical tube with a circular cross-section and an axisymmetric blockage (Figure 1). The selected diameter (3 mm) was based on the literature [40,41] and the length of the stenosis was defined as twice the normal diameter, an assumption applied by several researchers [42][43][44][45]. In addition, the length of the inlet zone (22 mm) was selected to ensure the creation of a fully developed inlet flow.…”
Section: Coronary Artery 3d Biomodels Design and Fabricationmentioning
confidence: 99%
“…The diameter selection was based on real data obtained by Zhou et al [38] in 2017. Moreover, to develop the stenotic area, it was found that several authors [2], [39], [40] consider the length of the stenosis as twice the normal diameter of the artery. In addition, the entrance length was chosen so that the velocity profiles could be fully established proximal to the stenosis throat.…”
Section: A Geometry Of the Stenotic Modelmentioning
confidence: 99%
“…The WSS is closely related to the development of atherosclerosis. For example, in the early stage of atherosclerosis, low and oscillatory WSSs that have stress values less than 1 Pa lead to inflammation and dysfunction of ECs, whereas, in the late stage, a WSS value of more than 7 Pa indicates erosion, which can be used to diagnose atherosclerosis [ 89 , 90 , 91 , 92 , 93 , 94 ].…”
Section: Diagnostic Indicators For Atherosclerosismentioning
confidence: 99%